I need help with thisone
solve:
((x)/(5x+10))+ ((x-3)/(x+2)) = (7)/(5)
Let's take that first part:
(x)/(5x+10)
In the denominator, factor out "5" That leaves that part as:
x/(5(x+2))
So now we have:
((x)/5(x+2)) + ((x-3)/(x+2)) = 7/5
We can multiply BOTH sides by 5 to leave the first denominator as simply "x+2"
x/x+2 + 5x-15/x+2 = 7
Now, multiply both sides by "x+2" to get a variable out of the denominator:
x+5x-15 = 7(x+2)
Can you get it from there?
To be honest, I spent forever on this question. I don't know why, but I kept coming up with the same wrong answer. I clicked off it and went back to it and it worked this time.
Would love to know what I did wrong before. :)
Matt
I CAME OUT WITH X= -29